Valvular heart disease in Antiphospholipid antibody syndrome: Isolated Tricuspid stenosis. Issue 3 (6th January 2019) - Kulkarni, Suraj Kumar; Moorthy, Nagaraja; Ramalingam, Rangaraj
Abstract : Antiphospholipid antibody syndrome (APLS) is a rare disorder characterized by a hypercoagulable state. Manifestations include arterial or venous thrombosis, recurrent fetal wastage, coronary artery disease, valvular heart disease, dilated cardiomyopathy, pulmonary artery hypertension, and intracardiac thrombus. Most commonly mitral valve is affected followed by aortic and then tricuspid valve. In this report, a rare case of spontaneous aortic thrombosis with tricuspid stenosis uncomplicated by other valve lesions is presented with clinical and echocardiographic studies and computed tomographic images.